Padusan Pacet Mojokerto Tourism Object Development Strategy to Improve Community Welfare - Jiono Jiono; Erwan Aristyanto (WORLDVIEW ( Development economic and sharia studies journal ), 2024)
Tourism development is the key to the success of Mojokerto Regency as a developing city, which is able to transform Mojokerto Regency as a tourism destination as well as a tourist destination. The development strategy in Mojokerto district which was developed based on tourism destinations is closely related to the concept of defense economics so that it places the community as the main actor. The problem that then arises is that tourism development has implications for the welfare of the people of Mojokerto Regency. The trend of increasing local original income over the last five years has enabled the potential of the Mojokerto Regency tourism sector as an alternative for alleviating poverty as well as increasing community welfare. The research aims to analyze new tourism objects in Mojokerto Regency as well as increasing new economic sectors through tourism activities in each sub-district in the Mojokerto City area. The research used qualitative methods through interviews and observations at Mojokerto Regency Government levels as a tourist destination as well as group discussions with residents. The research results show that the tourism sector contributes to the welfare of Mojokerto Regency, especially equal distribution of income as well as regional cash income, however the facilities and infrastructure as well as tourism infrastructure still need to continue to be improved so as to attract more visitors to Mojokerto Regency.